The Object (Subject) of a Criminal Assault as an Element of Criminalistics Characteristic of Crimes - A. Bessonov (Oriental Studies, 2018)
For over half a century criminalistics characteristic of crimes has served as the information foundation, the ‘root’ for the formation of private investigation practices for any given crime. In this sense there is no alternative to it and there is unlikely to be any. It defines the investigation algorithm in each particular situation and the specific features of certain investigatory actions. This is the point of view that the majority of Russian forensic scientists cling to. The object of a criminal assault plays one of the key roles in the structure of criminalistics characteristic of crimes. It is interrelated to other elements of this structure. The choice of an object of a criminal assault is determined by the specific features of the identity of a criminal. The object of a criminal assault determines at the same time the choice of a crime manner, its situation and the time of committing the crime. The manner of committing a crime in a certain situation is embodied in the form of specific trace evidences. Consequently, an investigator or an interrogating officer can determine, primarily, the scope of possible suspects by examining the data on trace evidences on the site of a crime, special features of the object of a criminal assault, as well as the place and time of the crime during the investigation process. Besides, the information on the special features of the object of a criminal assault make it possible to determine the manner of committing the crime; sources of evidence on the circumstances of the crime and the affiliate person; time and place of committing the crime, its motive and intent; direction of search for the information on the unidentified victim; typical trace evidence, left on the victim as a result of the crime or left by the victims themselves in the crime situation; causes and conditions that have facilitated the commission of the crime. Typical forensic-psychology model of a crime victim based on the analysis of investigative and court practice has an essential role in the determination of the criminal who has committed a crime. Therefore, information about the object of a criminal assault as an element of the criminalistics characteristic of crimes makes it possible for an investigator or an interrogating officer to realize its organizational scheme during investigation as follows: ‘from the victim’s identity (characteristics of the object of a criminal assault) - to the perpetrator’. The findings stated above can be confirmed by the author’s examination of ca. 3 thousand criminal cases on illegal fishing.